2021
DOI: 10.1007/s11104-021-05161-y
|View full text |Cite
|
Sign up to set email alerts
|

Increasing nitrogen supply to phosphorus-deficient Medicago sativa decreases shoot growth and enhances root exudation of tartrate to discharge surplus carbon dependent on nitrogen form

Abstract: Carboxylate release by roots has been considered a strategy for mobilization and acquisition of phosphorus (P). However, recently, it was argued that carboxylate release may be a way to discharge surplus carbon produced under conditions that limit plant growth. Plant P status may not be the main factor driving carboxylate release by roots. Instead, plant nitrogen (N) status and/or N:P ratio of the soil or plant may play a more important role in enhancing carboxylate release. MethodsA greenhouse pot experiment … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…MIP50 corresponds to the amount of unsterilized soil (which contains mycorrhizal microorganisms) needed to mycorrhize 50% of plants, which explains the correlation of PIM50 with nitrogen and phosphorus, mycorrhizal symbiosis improves the amount of these two elements in the soil (Vanek and Lehmann, 2014;Dejana el al., 2022). He et al (2021) found that Medicago sativa improves significantly the nitrogen and phosphorus amount in soil rich in mycorrhizal propagules and rhizobia.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
“…MIP50 corresponds to the amount of unsterilized soil (which contains mycorrhizal microorganisms) needed to mycorrhize 50% of plants, which explains the correlation of PIM50 with nitrogen and phosphorus, mycorrhizal symbiosis improves the amount of these two elements in the soil (Vanek and Lehmann, 2014;Dejana el al., 2022). He et al (2021) found that Medicago sativa improves significantly the nitrogen and phosphorus amount in soil rich in mycorrhizal propagules and rhizobia.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
“…Release of carboxylates is therefore widely considered to be part of a P-acquisition strategy that allows plants to survive in low-P environments (Lambers et al 2006(Lambers et al , 2011. However, several observations are inconsistent with this interpretation, such as increased carboxylate exudation at low N availability (Zhu et al 2016) and inconsistent relationships between rates of carboxylate release and both P uptake and plant growth (Huang et al 2017;He et al 2021;Wang and Lambers 2020). Carboxylate exudation by roots of alfalfa (Medicago sativa) growing in an alkaline soil low in both N and P was studied by He et al (2020He et al ( , 2021.…”
Section: Carboxylate Exudationmentioning
confidence: 99%
“…However, several observations are inconsistent with this interpretation, such as increased carboxylate exudation at low N availability (Zhu et al 2016) and inconsistent relationships between rates of carboxylate release and both P uptake and plant growth (Huang et al 2017;He et al 2021;Wang and Lambers 2020). Carboxylate exudation by roots of alfalfa (Medicago sativa) growing in an alkaline soil low in both N and P was studied by He et al (2020He et al ( , 2021. Root exudation of carboxylates (particularly tartrate) decreased with increasing P availability but also increased exponentially with increasing shoot N concentration.…”
Section: Carboxylate Exudationmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding ZnO did not signi cantly in uence the exudation of any of the carboxylates detected, while soil Cd level only signi cantly affected the exudation of tartrate. Increased tartrate exudation by alfalfa is mainly a response to P de ciency, or increased N to P ratio(He et al 2021a;He et al 2021b). The effects of Zn and Cd on carboxylate exudation by alfalfa roots were small, especially when P was supplied(He et al 2020a;He et al 2021a).…”
mentioning
confidence: 99%